"They tippy toe around the race issue": The impact of a Title IV‐E program on culturally informed practice for child welfare students. Issue 4 (16th March 2017) - Greeno, Elizabeth J.; Fedina, Lisa; Rushovich, Berenice; Moore, Jessica E.; Linsenmeyer, Debra; Wirt, Christopher
Abstract: This study examines changes in MSW students' perceived cultural competence across 11 child welfare practice skills before and after participation in a University's Title IV‐E program and explores students' perceptions of cultural competency and cultural humility. The findings indicate modest gains across all 11 practice skills; however, focus group interviews revealed that students do not necessarily feel prepared to conduct culturally competent practice with children and families. A culturally informed practice in public child welfare is discussed and includes training implications for Title IV‐E programs.